Building capacity of university educators to work with open practices beyond OER: a case study - Nascimbeni, Fabio; Burgos, Daniel (12th International Technology, Education and Development Conference (INTED), 2021)
Adopting open practices in higher education bears the potential to increase quality, access and effectiveness of the educational offer of universities, as well as to improve their impact on society and reputation. Because of this, an increasing number of universities are working to mainstream the adoption of open approaches among their staff, mainly by promoting the use of open content, for example supporting their lecturers in developing Open Educational Resources (OER) or MOOCs. On the other hand, few institutions are supporting their teaching staff in adopting open practices beyond content, promoting for instance the adoption of open learning design practices, open teaching and open assessment. This approach is reflected in research on open education. If we look at scientific literature, despite the many indications that research on open education should shift its focus from open content towards a more holistic understanding of openness (including research data, licensing, technology, etc.), it appears that existing attempts to analyse openness within universities are also typically limited to open content. In order to narrow down the gap in literature, the present paper analyses the level of open practices adoption of a case-study university by taking into account a number of dimensions of openness-open design, open content, open teaching and open assessment, allowing to reach a comprehensive view of the level of opened fluency of an institution. By analysing the data collected within an Italian university, based on a cohort of 181 educators, the paper discusses the adoption of open practices within the university in terms of open design, open content, open teaching and open assessment, relating those to the characteristics of the respondents. Based on these results, the paper concludes that educators seem to select their entry point into openness depending on their preferences and on the way they interact with the institutional, technological and time constrains connected to the adoption of open practices. Because of this, any initiative aimed to mainstream the use of open practices within universities should work beyond the support to open content production, to allow the multiplicity of approaches towards openness to emerge and to build on existing capacities of staff across all dimensions of openness.
Keywords: open education; OER; higher education; teachers training; capacity building; WOS(2)